Image states of Ag on Au(111) - Reuss, Christian; Wallauer, Wolfgang; Fauster, Thomas (Surface Review and Letters, 1996)
The image states for thin Ag layers on Au(111) have been studied with two-photon photoemission. The energies of the states show the behavior characteristic for a layer-by-layer growth of large terraces with their characteristic local work function. Image states with rather large linewidths are observed at energies outside the band gap of the projected bulk band structure. The identification of the states is complicated by the dominating signal from the occupied surface state.